Weak localization and interaction effects in acceptor graphite intercalation compounds - Prokopov, O.I.; Ovsiienko, I.V.; Matzui, L.Yu.; Len, T.A.; Naumova, D.D.; Berkutov, I.B.; Mirzoiev, I.G.; Normand, F. Le (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The presented work is devoted to investigations of manifestation of quantum effects of weak localization and interaction of charge carriers in electrical conductivity of acceptor graphite intercalation compounds (CICs). As shown by studies intercalation leads to a decrease in the resistivity and to change the resistivity temperature coefficient from negative sign in the source graphite on a positive sign in intercalated graphite. At the low temperature for all GICs specimens the minimum in the temperature dependence of resistivity is observed. In terms of the model of charge carrier’s weak localization and interaction for two-dimensional systems temperature dependence of phase relaxation time, localization radius and charge carriers screening constant for all GICs are estimated.